Redescription of Neocypridella fossulata (Daday, 1910) (Crustacea: Ostracoda) and description of a new subfamily - Savatenalinton, Sukonthip (Zootaxa, 2022)
Neocypridella fossulata (Daday, 1910) is redescribed based on type material from the Daday collection (Hungarian Natural History Museum, Budapest). The major diagnostic characters of the genus are the ovate shape of the carapace in lateral view, with the left valve overlapping the right valve, the absence of marginal septa on the valve margins, the right valve anterior selvage not inwardly displaced, the presence of a Wouters’ organ on the first antenna, the divided penultimate segment of the second antenna, the markedly large β-seta on the mandibular palp, the subquadrate terminal segment of the maxillula palp, the divided penultimate segment of the second thoracopod with setae d1 and d2 both long, the slender caudal ramus and the slender caudal ramus attachment with thin dorsal and ventral branches. Neocypridella fossulata can be further characterized by the oblique carapace in frontal view, the two smooth bristles on the maxillula third endite and the thin and long Ga claw of the caudal ramus, which is c. 3/5 of the length of the ramus.                The morphology of Neocypridella is compared with related taxa and the taxonomic position of the genus is discussed. This revealed that Neocypridella cannot be assigned to any of the extant subfamilies in the Cyprididae. Therefore, a new subfamily, Neocypridellinae subfam. nov., is erected.